The Relationship Between Body Mass Index (BMI) And The Incidence Of Dysmenore In Female Students At Pgri 37 Jakarta Vocational School - Indriyani, Dwi Sarin; Indrayeni, Roza (Universitas Prima Indonesia, 2025)
Female students who are menstruating frequently complain about pain, commonly known as dysmenorrhea. Dysmenorrhea cases in each country exceed 50%, with Indonesia having an average of 64.25%. Dysmenorrhea can be caused by a variety of reasons, including nutritional deficiencies, irregular menstrual cycles, menarche before the age of 12, heavy monthly flow, and smoking. Preliminary tests on 10 students at SMK PGRI 37 Jakarta revealed that five of them had severe dysmenorrhea. The purpose of this study was to examine the relationship between Body Mass Index (BMI) and the incidence of dysmenorrhea in female students at SMK PGRI 37 Jakarta. This research is a quantitative study with a cross-sectional design. Sampling was conducted using the total sampling technique, with 58 female student respondents. The results showed that there was a relationship between Body Mass Index (BMI) and the incidence of dysmenorrhea in female students of SMK PGRI 37 Jakarta with a value of (P-value = 0.015). Based on these results, it can be concluded that abnormal BMI in female students impacts the severity of dysmenorrhea, so it is critical to eat nutritious foods and keep BMI within normal ranges.